THE EFFECT OF PRODCUT QUALITY AND PRICE ON THE PURCHASE DECISION OF MOLTO PEWANGI IN ALFAMART PEMURUS DALAM REGION OF BANJARMASIN - Mailiana, Mailiana; Budiati, Penta Lestarini (Jurnal Ekonomi dan Manajemen, 2022)
The purpose of this study was to determine the effect of product quality and price partially and simultaneously on the purchase decision of Molto Pewangi at Alfamart Pemurus of Banjarmasin. The population in this study was 247 consumers of Molto Pewangi products who bought Molto products in 2021. Samples could be taken from 10% to 20% if the population is large or more than 100 (Arikunto, 1998: 120). Hence, the number of samples taken in this study was 50 people with the calculation, namely: F = 20% x 247 = 49.4 rounded to 50. The results of the study are based on the t-test that the product quality variable has a significant value of 0.001 < 0, 05 means that the hypothesis is accepted that product quality has a partial effect on purchasing decisions. Meanwhile, the price variable based on the t-test obtained a value of 0.33 > 0.001 which means the hypothesis is rejected that the price has no partial effect on purchasing decisions. Based on the results of the f test above, it shows a significance value of 0.001 <0.05. and the regression model can be used for decision making or it can be said that product quality and price have a simultaneous effect on purchase decisions.